Yeast mannan increases Bacteroides thetaiotaomicron abundance and suppresses putrefactive compound production in in vitro fecal microbiota fermentation. Issue 10 (2nd October 2020) - Oba, Shunsuke; Washida, Kazuto; Shimada, Yu; Sunagawa, Tadahiro; Tanihiro, Reiko; Sugiyama, Hiroshi; Nakamura, Yasunori
ABSTRACT: Yeast mannan is a part of yeast cell wall and can potentially affect gut microflora as a soluble dietary fiber. We demonstrated that yeast mannan suppressed putrefactive production and increased the relative abundance of Bacteroides thetaiotaomicron in in vitro fecal fermentation. These results suggest that yeast mannan can be used as a novel prebiotic food ingredient.